Two-stage nodal network interdiction under decision-dependent uncertainty - Ahmadi Digehsara, Amin; Ardestani-Jaafari, Amir; Mazahir, Shumail; Fathi, Michel (Annals of operations research, 2024)
Infrastructures such as power stations, water systems, railways, highways, subway stations, and roads play an important role in ensuring that the network operates safely and effectively. In this study, we aim to develop a fortification plan to protect the nodes and links from destructive attacks. However, there is often a degree of uncertainty concerning the exact location or degree of the attack. To address this problem, we suggest a trilevel robust shortesth path problem based on the defender–attacker–defender model. In this model, the primary defender provides protection plan against attacks, while the attacker identifies weaknesses and attacks non-fortified components. Lastly, the inner defender determines the shortest path between the source and sink of the interdicted network. To solve the problem efficiently, we resort to a column-and-constraint generation algorithm. Several benchmark examples from the literature are used to demonstrate the effectiveness of our model. Despite the inherent complexity of the problem, we demonstrate that using careful analysis of worst-case attack scenarios, we can develop a successful fortification plan within a reasonable computational time.